Sea‐level haemoglobin concentration is associated with greater exercise capacity in Tibetan males at 4200 m. Issue 11 (1st November 2015) - Wagner, P. D.; Simonson, T. S.; Wei, G.; Wagner, H. E.; Wuren, T.; Qin, G.; Yan, M.; Ge, R. L.
Abstract : New Findings: What is the topic of this review? Recent developments link relatively lower hemoglobin concentration in Tibetans at high altitude to exercise capacity and components of oxygen transport. What advances does it highlight? Haemoglobin concentration (ranging from 15.2 to 22.9 g dl −1 ) in Tibetan males was negatively associated with peak oxygen (O2 ) uptake per kilogram, cardiac output and muscle O2 diffusion conductance. Most variance in the peak O2 uptake per kilogram of Tibetan males was attributed to cardiac output, muscle diffusional conductance and arterial partial pressure of CO2 . The mechanisms underlying these differences in oxygen transport in Tibetans require additional analyses. Despite residence at >4000 m above sea level, many Tibetan highlanders, unlike Andean counterparts and lowlanders at altitude, exhibit haemoglobin concentration ([Hb]) within the typical sea‐level range. Genetic adaptations in Tibetans are associated with this relatively low [Hb], yet the functional relevance of the lower [Hb] remains unknown. To address this, we examined each major step of the oxygen transport cascade [ventilation (VE), cardiac output (QT) and diffusional conductance in lung (DL) and muscle (DM)] in Tibetan males at maximal exercise on a cycle ergometer. Ranging from 15.2 to 22.9 g dl −1, [Hb] was negatively associated with peak O2 uptake per kilogram ( r  = −0.45, P  < 0.05) and both cardiac output (QT/kg: r  = −0.54, P  < 0.02) and muscle O2 diffusion conductance (DM/kg: r  = −0.44, P  < 0.05) but not ventilation, arterial partial pressure of O2 or pulmonary diffusing capacity. Most variance in peak O2 uptake per kilogram was attributed to QT, DM and arterial partial pressure of CO2 ( r 2  = 0.90). In summary, lack of polycythaemia in Tibetans is associated with increased exercise capacity, which is explained by elevated cardiac, muscle and, to a small extent, ventilatory responses rather than pulmonary gas exchange. Whether lower [Hb] is the cause or result of these changes in O2 transport or is causally unrelated will require additional study. Abstract :